Evaluating the effect of different management policies on the long-term sustainability of irrigated agriculture. (July 2016) - Singh, Ajay
Abstract: Rise in groundwater level followed by waterlogging and secondary salinisation has become a serious problem in canal irrigated areas of arid and semiarid regions of the world. A wide range of solutions could be considered to address the problems. But the effectiveness of all the solutions and their combinations cannot be verified with on-farm experiments. Simulation models by way of their predictive capability are often the only viable means of providing input to policy decisions. To combat the problem, the computer based simulation model, SaltMod was applied in a waterlogged area of northwest India in which over 500, 000 ha has already waterlogged resulting in reduced crop yield and abandonment of agricultural lands. After successful calibration and validation, several alternative management policies were studied for their long-term impacts on groundwater levels and salinities. The alternative policies revealed that the groundwater levels in the study area would continue to rise in the long-run under the existing conditions. Thus, suitable water management strategies such as changes in cropping patterns with reduced rice area, reduced canal water use, increased groundwater use, and canal lining are suggested to bring the groundwater level down to a safe depth and to prevent further rising of the groundwater level.